Political Diplomacy, Religion and Culture: Analysing Iran's Geopolitical and Ideological Interests in Indonesia - Hannase, Mulawarman; Hamzah, Idil (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2025)
This article discusses Iran’s geopolitical and ideological interests in Indonesia within the context of international relations and cultural diplomacy. As a country with Shiite-based ideological power and regional geopolitical ambitions, Iran views Indonesia—the world’s largest Muslim-majority nation—as a strategic partner to expand its influence. This study employs a descriptive qualitative approach through literature review and secondary data analysis to examine Iran's strategies in building relationships via educational, cultural, and economic cooperation institutions. The findings show that Iran’s strategy in Indonesia reflects a blend of soft diplomacy and geopolitical interests aimed at strengthening Iran’s position in Southeast Asia. However, Iran’s ideological penetration faces resistance from Indonesia’s Sunni-majority population and domestic political dynamics that emphasize religious moderation and national stability.